Hubungan Stigma Gangguan Jiwa dengan Perilaku Masyarakat Pada Orang dengan Gangguan Jiwa di Wilayah Kerja Puskesmas Karya Wanita Pekanbaru - Usraleli Usraleli; Dedek Fitriana; Magdalena Magdalena; Melly Melly; Idayanti Idayanti (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Stigma is one of the inhibiting factors in healing people with mental disorders. Many people do not behave well in people with mental disorders and the public does not care about people with mental disorders. Community understanding of mental disorders is very minimal, this causes sufferers to get unpleasant attitudes from the community and from their own families. The aim was to find out the relationship between the stigma of mental disorders and community behavior in people with mental disorders (ODGJ) in the work area of KaryaWanita Community Health Center RW 07 Pekanbaru in 2019. The design of this study was descriptive analytic  withaapproach cross sectional with a sample of 68 respondents with criteria that were has been established. The instrument in this study was a questionnaire. The results of this study have a significant relationship between the stigma of mental disorders and community behavior in ODGJ in people's knowledge and attitudes. Knowledge is closely related to stigma towards ODGJ (ρ value = 0.013 and OR = 0.067). The meaning of the community that has a negative stigma of mental disorder has a chance of 0.067 times to have bad knowledge on ODGJ. The attitude is closely related to stigma towards ODGJ (p value = 0.017 and OR = 9.2). That meanspeople who have the stigma of negative mental disorder have a chance 9.2 times to have a bad attitude towards ODGJ. It was concluded that there was a significant relationship between the stigma of mental disorders and community behavior in people with mental disorders in the work area of Karya Wanita RW 07 Pekanbaru in 2019. It was recommended to the puskesmas to improve socialization regarding the attitude and initial handling of mental disorders to the community.